The Role of Physical Activity in Improving QOL of Patients Undergoing Hemodialysis - Ferdiana, Asihanti Rosita; Samsu, Nur (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2024)
Patients undergoing hemodialysis (HD) experience increased mortality rates and decreased physical activity, which has an impact on patients' low quality of life (QOL). Physical activity has positively affected cardiovascular function, strength, and overall health status. On the other hand, physical activity has not been proven to cause any health hazards in HD patients. However, physical activity has not become a routine practice for HD patients, and there are no clear guidelines for physical activity in HD patients. Due to the inherent condition, intradialytic aerobic exercise appears to be the most suitable physical activity method for HD patients. However, research is still needed to assess the effectiveness and safety of intradialytic exercise (IDE) for HD patients in the long term. Research results can be used as a reference in developing the most appropriate IDE guidelines for HD patients.